The past in the present : women's higher education in the twentieth-century American South - McCandless, Amy Thompson, 1946- (University of Alabama Press, 1999)
The history of higher education in the 20th-century South, like the history of the region, both mirrors and diverges from the national pattern. Not surprisingly the region's demographic, economic, social, political, and cultural characteristics have accounted for many of the variations between the education of southern women and women in the rest of the nation. Southern students, McCandless finds, have generally been more Protestant, more rural, more conservative, and less affluent than their northern and western counterparts. Southern institutions have been slower to raise matriculation and graduation standards and to revise the classical curriculum. Southern administrators and legislators have opposed coeducation and integration longer and harder than college officials elsewhere. Certain types of institutions, such as all-black colleges, public women's colleges, and separate agricultural colleges, have been more prevalent in the South. Although many of these differences are not gender-specific, all have contributed to the distinctive educational experience of women in this region. Much has been written on the distinctiveness of this region, but virtually nothing has been published on the education of women in the South. By focusing on both black and white women at a wide variety of institutions and drawing on oral interviews and campus publications as well as traditional histories, McCandless is able to construct a more detailed picture of women's collegiate experiences in the 20th-century South than those provided by general studies that rely primarily on materials from the North and Midwest. -- Provided by publisher.